Manufacture and thermal deformation analysis of semicrystalline polymer polyether ether ketone by 3D printing. (August 2014) - Wu, W. Z.; Geng, P.; Zhao, J.; Zhang, Y.; Rosen, D. W.; Zhang, H. B.
Abstract : This study developed a polyether ether ketone (PEEK) three-dimensional (3D) printing system. Three-dimensional printing chamber is designed for researching and solving the thermal deformation problem of the fabricating high melting point biomaterial PEEK process through 3D printing. A multi-parameter single factor experiments were carried out to analyse the effect of chamber temperature T 1, nozzle temperature T 2 on deformation of PEEK 3D printing samples. The results prove that the warping deformation is minimal with the chamber temperature at 130°C, the nozzle temperature at 350°C. The PEEK parts were printed successfully through the optimal parameters determined by the experiment. The results of this study demonstrate the feasibility of manufacturing personalised small batch PEEK function parts in industrial and medical fields.